BIOGRAPHY VISUALIZATION OF SULTAN THAHA SAIFUDDIN BASED ON ARCGIS STORY MAPS IN JAMBI PROVINCE - Hendra Gunawan; Muhammad Azir; Dodi Harianto; Abdul Halim (Department of Geography Education, Faculty of Social Sciences, Universitas Negeri Medan, 2021)
The introduction of new technologies for historical studies presents an opportunity to make historical studies more accessible to the public. The ArcGIS platform has facilitated this effort and offers interesting ways to do this, including the Story Map program. Part of the cloud-based online ArcGIS platform, the story map application enables the integration of narratives, images, and maps in an easy-to-use format. This paper tries to apply this technology in the theme of Visualization of Biography of Sultan Thaha Saifuddin Based on ArcGIS Story Map in Jambi Province. Many similar writings discuss the biography of Sultan Thaha Saifuddin with a historical approach but do not look at it from a spatial perspective. The focus of historical research only focuses on events and periodization. Therefore, this article describes the biography of Sultan Thaha Saifuddin so that other historians can also apply this technology to their work.